Study on the pneumatic hammer phenomenon of aerostatic bearings based on the empirical mode method: Numerical and experimental analysis. (March 2023) - Wang, Peng; Zhang, Yingjie; Feng, Libo; Hou, Weijie; Wang, Jianwei; Li, Wenjun; Feng, Kai
Abstract: Aerostatic bearings are widely used in ultra-precision equipment machines due to their notable advantages, including low friction, high accuracy, and pollution-free characteristics. However, the pneumatic hammer phenomenon in aerostatic bearings is harmful for processing and measuring accuracy. By comparing the predicted results and the experimental measurements, a new perspective has been presented in this paper to identify the characteristics of the pneumatic hammer. The empirical mode method (EMD) is applied to decompose and extract intrinsic mode function (IMF) components of pressure fluctuation acquired from CFD calculations. The theoretical results show that the pneumatic hammer of aerostatic bearings relies on the frequency characteristics between the natural frequency of bearing-load system and the pressure fluctuation frequency in the recess. Besides, a single-degree-freedom test rig as well as a double-degree-freedom test rig are set up to explore the pneumatic hammer. The experimental results show a remarkable agreement with predictions. Comparisons of measurements and predictions reveal that the calculated natural frequency and the decomposed IMFs frequencies of pressure fluctuations are reliable to estimate the onset condition of the pneumatic hammer instability.